Teacher’s perspectives in the use of technology in ESP language classroom - Farida Ulfa; Atiqah Nurul Asri (Jurnal Linguistik Terapan, 2017)
The integration of technology in a language classroom practice is effective, as shown by various researches around the globe. The ability in using technology in the language classroom also signifies the high quality a teacher has. This in turn will have a meaningful impact in the effectiveness of the teaching and learning process.However, in what ways the technology is used and how it is normally applied in the teaching and learning process is yet unknown. The obstacles in using the technology properly and also what kind of technology is used also become issues.This study is aimed at identifying to which extent the four English language teachers in Politeknik Negeri Malang, particularly in the Department of Information Technology, implement the technology, i.e. the use of the internet, computer, and other supporting devices in their ESP classrooms. Furthermore, the study also analyses the factors that demand the use of technology in ESP classrooms and how they can be used as a means of self-reflection for the teachers to evaluate their teaching and learning approaches to improve the students' English mastery.